Analysis of 1X2 MIMO Antenna for 6G Communication Systems - Sindhuja, N. M. Mary; Ramalakshmi, P.; Rajeswari, J.; Rajalakshmi, J.; Anitha, P.; Sudhakar, G.; Sureshbabu, R. (Journal of Neonatal Surgery, 2025)
The design and construction of a compact, 1 × 2 hexagonal patch Multiple Input Multiple Output (MIMO) antenna for upcoming 6th Generation (6G) wireless communication applications is presented in this paper. The suggested antenna supports high-data-rate and extremely dependable communication by operating at a core frequency of 12 GHz, which covers a large spectrum. A redesigned Hilbert space filling curve serves as the foundation for the antenna elements, guaranteeing improved radiation efficiency, gain and bandwidth. An integrated design uses a space filling curve-based hexagonal antenna to produce low Envelope Correlation Coefficient (ECC < 0.001), good isolation (>25 dB) with a low loss FR4 epoxy substrate (εr = 4.4), with thickness of 1.6 mm the antenna has an ideal total active reflection coefficient (TARC<0dB), a high diversity gain (DG > 9.98 dB), and a return loss of -10dB. The simulated results verify that the suggested 1 × 2 MIMO antenna is appropriate for 6G applications, high-speed data transfer and next-generation wireless networks operating at 12GHz.